Building Global Teaching Capacity Among Pre-Service Teachers: Epistemological and Positional Framing in an Internationally Paired, Authentic Practicum. (May 2023) - Kurup, Premnadh M.; Nethsinghe, Rohan; Li, Xia; Cherian, Jose; Yang, Yunying
Building the capacity of pre-service teachers to work in globalized cross-cultural environments is essential to cope with the challenges of the 21st century. This study establishes the value of internationally paired, authentically collaborative practicums with strong epistemological and positional framing in pursuing such capacity development. It was conducted among 90 pre-service teachers from three different universities in Australia and India who participated in a three-week paired practicum in three schools in India. The practicum included the collaborative production of an integrated Australian and Indian combined theme presented in a whole school forum. Mixed methods and a design-based research approach yielded data affirming that such a model did indeed provide pre-service teachers with the confidence to teach in increasingly diverse classrooms and contexts, while also identifying which aspects of this practicum model were most influential in this regard.